2009
DOI: 10.1108/09555340910986664
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and prioritizing critical intellectual capital for e‐learning companies

Abstract: Purpose -The purpose of this paper is to identify and prioritize the measures of intellectual capital (IC) of e-learning service companies that ultimately influence firms' competitive advantages. Design/methodology/approach -Through focus group interviews, content analysis, and the analytic hierarchy process, this paper identifies five dimensions and 15 indicators to measure the IC of e-learning service companies in Taiwan. Findings -The findings and prioritization of ICs can help the e-learning companies to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 48 publications
1
19
0
1
Order By: Relevance
“…According to Dumay and Cai (2014), some novel sources of text used in ICD CA studies are "price sensitive announcements to the Australian Stock Exchange (Dumay and Tull, 2007), competency standards of an accounting firm (Chang and Birkett, 2004) and transcripts of focus group meetings (Chen, 2009)".…”
Section: A Body Of Text and A Research Questionmentioning
confidence: 99%
“…According to Dumay and Cai (2014), some novel sources of text used in ICD CA studies are "price sensitive announcements to the Australian Stock Exchange (Dumay and Tull, 2007), competency standards of an accounting firm (Chang and Birkett, 2004) and transcripts of focus group meetings (Chen, 2009)".…”
Section: A Body Of Text and A Research Questionmentioning
confidence: 99%
“…Structural capital is the repository of knowledge that is accessible through various sources that allow for knowledge sharing and knowledge creation between the members (Chang & Birkett, 2004). An organization's structure (SC) affects the development of IC due to its role as the supportive element for human capital (Chen, 2009). For example, research revealed a multiplicative effect between SC, when it supports HC, and results in improved enterprise performance.…”
Section: Structural Capital (Sc)mentioning
confidence: 99%
“…This phase also emphasised the dynamic aspects of intellectual capital (Kianto, 2007;Montemari and Nielsen, 2013;de Santis, 2016): in creating value as exemplified by IC navigators (Fernström et al, 2004;Roos et al, 2005), value creation maps Marr, 2008), combinations of both (Cuganesan and Dumay, 2009;Jhunjhunwala, 2009), knowledge asset value spiral (Carlucci and Schiuma, 2006), the analytical hierarchy process (Liu, 2006(Liu, , 2007(Liu, , 2010aCarlucci and Schiuma, 2007;Grimaldi and Cricelli, 2009;Chen, 2009;Asonitis and Kostagiolas, 2010;Chang et al, 2010;Lee, 2010) and the further development of the analytical hierarchy process into the Conjoint Value Hierarchy approach (Pike and Roos, 2004;Roos et al, 2005;Garnett et al, 2008;Millar et al, 2010), strategy maps (Kaplan and Norton, 2004), and causal performance maps (Abernethy et al, 2005), of which the two latter were not developed specifically for intellectual capital applications but include aspects of intellectual capital when used. In addition, there was greater insights into the role of intellectual capital within differing strategic logics, i.e.…”
Section: Intellectual Capitalmentioning
confidence: 99%